Occurrence of euchromatic B chromosomes in natural populations of Moenkhausia bonita and M. forestii (Pisces: Characidae) - Ranucci,Leandro (2021)
ABSTRACT Moenkhausia is a highly specious genus among the Characidae, composed of 96 valid species. Only twelve species have a known karyotype. Thus, here are presented the first cytogenetic data of two allopatric populations of Moenkhausia bonita and one of M. forestii, both belonging to the upper Paraná River basin (PR) with discussion on the evolutionary and cytotaxonomic aspects of the genus. The two species presented 2n = 50 chromosomes but different karyotype formulas and occurrence of 1-2 B chromosomes. These elements are small metacentrics in M. bonita and small acrocentrics in M. forestii. In both species, B chromosomes were euchromatic. Ag-NOR sites were found in pair 3 (metacentric), coinciding with fluorescent in situ hybridization (FISH) by the 18S rDNA probe in both species. However, the species differed in terms of the number and position of 5S rDNA sites. Heterochromatic blocks, mapped in M. bonita showed the least amount of heterochromatin in the terminal and pericentromeric regions, while the M. forestii karyotype revealed a greater amount of interstitial heterochromatic blocks. The karyotype distinctions between the two species, including the morphology of B chromosomes, may contribute as a reference in the taxonomic studies in this group.